Risk factors for implant failure after fixation of proximal femoral fractures with fracture of the lateral femoral wall. Issue 2 (February 2018) - Gao, Zhechen; Lv, Yang; Zhou, Fang; Ji, Hongquan; Tian, Yun; Zhang, Zhishan; Guo, Yan
Abstract: Introduction: To investigate potential predictors of implant failure following fixation of proximal femoral fractures with a fracture of the lateral femoral wall. Materials and methods: Medical records of 99 adult patients who had operative treatment for a proximal femoral fracture with a fracture of the lateral femoral wall between May 2004 and April 2015 were retrospectively analysed to determine factors associated with implant failure. Patients underwent routine surgical procedures for implantation of extramedullary or intramedullary devices. Potential predictors were age, gender, body mass index, comorbidities, type of fracture, reduction method, status of greater and lesser trochanters, course of the lateral fracture line, and presence/absence of a free bone fragment at the junction of the greater trochanter and lateral femoral wall. Results: Ten (10%) implant failures were identified. Univariate analysis identified a free bone fragment at the junction of the greater trochanter and lateral femoral wall (odds ratio [OR], 21.25; 95% confidence interval [CI], 4.31–104.67; p <  0.001) and a transverse fracture line across the lateral femoral wall (primary or iatrogenic) (OR, 5.36; 95% CI, 1.29–22.30; p  = 0.021) as factors associated with implant failure. Using a multivariate model, only a free bone fragment at the junction of the greater trochanter and lateral femoral wall (OR, 16.05; 95% CI, 3.06–84.23; p  = 0.001) was a risk factor for implant failure. Conclusions: A free bone fragment at the junction of the greater trochanter and lateral femoral wall and a transverse fracture line across the lateral femoral wall are predictors of implant failure in proximal femoral fractures with a fracture of the lateral femoral wall. Integrity of the lateral femoral wall correlates with prognosis of proximal femoral fracture. Lateral femoral wall reconstruction may be required for effective treatment of proximal femoral fractures with a fracture of the lateral femoral wall.